A review of modeling pesticides in freshwaters: Current status, progress achieved and desirable improvements. (1st January 2023) - Centanni, M; Ricci, G. F; De Girolamo, A. M; Romano, G; Gentile, F
Abstract: This study comprises a critical review of modeling of pesticides in surface waters. The aim was to update the status of the use of models to simulate the fate of pesticides from diffuse sources. ISI papers were selected on Scopus and the information concerning the study areas, type of pesticides (herbicides, fungicides and insecticides), the model, and the methodology adopted (i.e., calibration and/or validation, spatial and temporal scales) were analyzed. The studies were carried out in Europe (55.5%), North America (22.3%), Asia (13.9%) and South America (8.3%). The Soil and Water Assessment Tool proved to be the most used model (45.95%). Herbicides were the most modeled pesticides (71.4%), followed by insecticides (18.2%) and fungicides (10.4%). The main herbicides modeled were atrazine, metolachlor, isoproturon, glyphosate, and acetochlor. Insecticides such as chlorpyrifos and metaldehyde. Chlorothalonil, and fungicides (i.e., tebuconazole) were the most widely investigated. Based on published studies, it was found that modeling approaches for assessing the fate of pesticides are constantly evolving and the model algorithms work well with diverse watershed conditions, management strategies, and pesticide properties. Several papers reported concentrations of pesticides exceeding ecotoxicological thresholds revealing that water contamination with pesticides used in agriculture and urban areas is a priority issue of current global concern. Graphical abstract: Image 1 Highlights: A critical review of modeling of pesticides in surface waters is reported. Modeling approaches for assessing the fate of pesticides are constantly evolving. SWAT was the one most used on a global scale (35.71%). Herbicides were the most modeled pesticides followed by insecticides and fungicides. Concentrations of pesticides exceed ecotoxicological thresholds.